2006
DOI: 10.1143/jjap.45.5590
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Monitoring of Cavity Filling in Nanoimprints by Capacitance

Abstract: This report deals with the feasibility of carrying out in-situ monitoring of cavity filling in nanoimprints using capacitance measurements with a capacitance circuit built-in on the mold body. A finite element model valid for the numerical description of a parallel-plate capacitor has been developed, and simulations were carried out to predict the influence of cavity filling on capacitance values. On the other hand, in order to measure the continuous variations in capacitance of a parallel-plate capacitor duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…How to reduce pattern defect rates and acquire high pattern transferring fidelity has been studied by many researchers [4][5][6][7][8][9][10][11][12]. Although defects appearing during imprint process are well studied [4,5], less attention is paid to defects appearing in demolding process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How to reduce pattern defect rates and acquire high pattern transferring fidelity has been studied by many researchers [4][5][6][7][8][9][10][11][12]. Although defects appearing during imprint process are well studied [4,5], less attention is paid to defects appearing in demolding process.…”
Section: Introductionmentioning
confidence: 99%
“…Although defects appearing during imprint process are well studied [4,5], less attention is paid to defects appearing in demolding process. Of those, Park et al demonstrated that an optimal temperature leading to minimal deformation of molded resist existed for demolding via both experimentation and numerical simulation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although considerable work has been performed with regard to the models and explorations on the polymer flow behavior based on continuum mechanics, 3-6 molecular dynamics simulations [7][8][9] and experiments. [10][11][12][13] However, the deformation mechanism of the polymer is still difficult to characterize and predict due to the structure complexity of the polymer and the multiplicity of influential factors-thermo-mechanical processing history, time-dependent behavior, anisotropy, etc. And continuum mechanics fails to research the polymer filling behavior when the feature size drops to below several tens of nanometers.…”
Section: Introductionmentioning
confidence: 99%
“…So, the development and application of MIL urgently require in-depth understanding of resist's microscale flow phenomena and filling mechanism. But, up to now, existing research with regard to the filling behavior of the thin resist films has been focused on the numerical simulations 6-9 and simplified theoretical models; 10,11 experimental approaches [12][13][14] are relatively rare. Although the research based on computational fluid dynamics (CFD) has been conducted for studying the microfluidics phenomena, experimental observations are still important because numerical simulations are mainly focused on the validation of physical models based on observed phenomenon.…”
Section: Introductionmentioning
confidence: 99%